Gene delivery into prostate cancer cells by holmium laser application - Sagi, Sreedhar; Knoll, Thomas; Trojan, Lutz; Schaaf, Axel; Alken, Peter; Michel, Maurice Stephan (Prostate cancer and prostatic diseases, 2003)
New approaches to treat prostate cancer (PCA) are utilizing gene therapy and aim to correct the disease at the genetic level. Getting a gene efficiently into the target cell is the subject of much interest. We used a holmium laser for transfecting rat PCA cells with the reporter gene pEGFP. By FACS analysis and fluorescence microscopy, we could demonstrate that cellular delivery of plasmid DNA was possible with high efficiencies up to 41.3%. Therefore, transfection of PCA cells by holmium laser might offer a promising new gene transfer strategy to PCA with minimal invasiveness.